2021
DOI: 10.3390/ijerph18030995
|View full text |Cite
|
Sign up to set email alerts
|

Ranking the Healthcare Resource Factors for Public Satisfaction with Health System in China—Based on the Grey Relational Analysis Models

Abstract: (1) Background: Public satisfaction with the health system is a very important comprehensive indicator. Given the limited healthcare resources in a society, it is always important for policymakers to have full information about the priority and the ranking order of the factors of healthcare resources for improving public satisfaction. (2) Methods: Grey Relational Analysis (GRA) is advantageous for satisfaction analysis because satisfaction is a “grey concept” of “having a clear boundary but vague connotation”.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…For example, Kose et al [13] identified the most livable Turkish city through the GRA. With the help of a GRA model, Peng et al [14] enumerated the health resources that satisfy the public in China.…”
mentioning
confidence: 99%
“…For example, Kose et al [13] identified the most livable Turkish city through the GRA. With the help of a GRA model, Peng et al [14] enumerated the health resources that satisfy the public in China.…”
mentioning
confidence: 99%
“…Gray relational analysis is a quantitative method used to judge whether the corresponding sequences are closely related according to the geometric similarity of sequence curves, which can measure the degree of association between factors. The calculation steps are as follows ( 70 , 71 ):…”
Section: Methodsmentioning
confidence: 99%
“…The basic idea of GRA is to conclude the degree of relationship between factors by comparing geometrical patterns of data (Javed et al, 2020b;Dong et al, 2018). GRA has been applied for solving supplier selection problems (Diba & Xie, 2019;Yang & Chen, 2006), temperature-disease transmissibility relationship analysis (Irfan et al, 2021), optimization of engineering processes (Obara et al, 2021), evaluations of barriers to university enrollment (Fahim et al, 2021) and healthcare resource factors (Peng et al, 2021), among others. The implementation of GRA then being applied to Grey Relational Grade (GRG) to estimate the count relation of factors (King & Wen, 2007).…”
Section: Supplier Selection Through Grey Relational Analysismentioning
confidence: 99%